Yang Terlupakan, Yang Berkarya: Tinjauan atas Peran Perempuan Jawa dalam Tradisi Rewang untuk Memahami Ulang Makna sebuah Karya - Lukas Eko Budiono (Indonesian Journal of Theology, 2017)
The tradition of rewang in Javanese society denotes the preparation and production of meals, a custom performed primarily by women. As a cultural value, rewang reflects an ideal standard for the role of women. In this essay, an assessment of the role of women is deployed to explore the meaning of work and, at the same time, to surface an understanding of hospitality that is based on the tradition of rewang, in order to demonstrate social meaning and values from the rewang tradition. Within this tradition, the meaning of work begins necessarily with remembering just how important is each person’s role. For members of the Javanese community, participation according to the rewang tradition shows the importance of strengthening blood-relationship with others (termed silaturahmi in Bahasa Indonesia). It is this blood-relation that serves as core value within the rewang tradition, such that rewang becomes a model for being community within the social context of Indonesia. By employing a perspective of rewang, this essay thus attempts to demonstrate how hospitality can serve as a basis for the identity of presence concerning the Javanese community.